2010
DOI: 10.1038/ijo.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss by a low-fat diet and a low-carbohydrate diet on peptide YY levels

Abstract: ObjectiveTo compare the effects of weight loss by an energy-restricted low-fat diet versus low-carbohydrate diet on serum peptide YY (PYY) levels.Design8-week prospective study of 30 obese adults (mean age: 42.8 ± 2.0 years, mean BMI 35.5 ± 0.6 kg/m2).ResultsAfter 8 weeks, subjects on the low-carbohydrate diet lost substantially more weight than those on the low-fat diet (5.8 kg vs. 0.99 kg, p<0.001). Weight loss by either diet resulted in a 9% reduction in both mean fasting serum PYY levels (baseline: 103.5 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 11 publications
6
40
1
2
Order By: Relevance
“…In general, if these signals change in the obese humans in response to energy-restricted weight loss, a collective signal favoring hunger over satiety/satiation is observed (Table 1). However, detection of this adaptive response is much less consistent than that of circulating adipose signals and nutrients, as they may be dependent on the presence of a negative energy balance (2,30,42,71,133), the amount of weight loss (71), the amount of physical activity (121), the specific derivative of the hormone measured [peptide YY(PYY) vs. PYY3-36; total vs. acetylated ghrelin] (18) or the type of macronutrient restricted in the diet (71,95). Even under the same conditions of weight loss and maintenance, there is a wide variability in individual responses with respect to these adaptations in hunger and satiety signals (18).…”
Section: The Gut: Sensing the Prandial Statementioning
confidence: 99%
“…In general, if these signals change in the obese humans in response to energy-restricted weight loss, a collective signal favoring hunger over satiety/satiation is observed (Table 1). However, detection of this adaptive response is much less consistent than that of circulating adipose signals and nutrients, as they may be dependent on the presence of a negative energy balance (2,30,42,71,133), the amount of weight loss (71), the amount of physical activity (121), the specific derivative of the hormone measured [peptide YY(PYY) vs. PYY3-36; total vs. acetylated ghrelin] (18) or the type of macronutrient restricted in the diet (71,95). Even under the same conditions of weight loss and maintenance, there is a wide variability in individual responses with respect to these adaptations in hunger and satiety signals (18).…”
Section: The Gut: Sensing the Prandial Statementioning
confidence: 99%
“…Of note, changes in leptin with weight loss have been shown to be predictive of weight regain and may therefore represent a key modulator of weight regain [21]. Gut-derived peptides such as ghrelin, PYY, and GLP-1 play important roles in the short-term meal-to-meal signaling of appetite and are also altered by weight loss, favoring and predicting increased food intake [21][22][23][24][25]. Gut peptide responses to weight loss, however, are variable likely due individual responsiveness to meals (macronutrients, fiber content, size), and thus may be a more or less important adaptive mechanism [25].…”
Section: Changes In Appetite-related Peripheral Signalsmentioning
confidence: 99%
“…124 Short-term gut-related peptides such as ghrelin, PYY, and GLP-1, which play important roles in the meal-tomeal signaling of appetite, are altered by weight loss, favoring increased food intake. [125][126][127][128] Recently, neuroimaging studies have shown that the weight-reduced state is associated with enhanced signaling in the motivation, reward, attention, and behavioral centers of the brain 129 -131 and that these brain responses respond to physiological signals such as leptin. 132 In summary, although caloric restriction results in shortterm weight loss, it is extremely difficult for individuals to maintain this weight loss over the long term.…”
Section: Changes In Energy Intakementioning
confidence: 99%